Cyanocharax alburnus (Hensel, 1870) (Characiformes: Characidae): first distribution record in Argentina - Protogino, Lucila Cristina (2012)
This note reports the presence of Cyanocharax alburnus in the Argentinian Mesopotamia. This represents the southern distributional limit for the species in South America and the first record for Argentina's fresh water fish fauna.